Genotype–Phenotype Correlation of Tracheal Cartilaginous Sleeves and Fgfr2 Mutations in Mice. (4th September 2020) - Lam, Austin S.; Liu, Carrie C.; Deutsch, Gail H.; Rivera, Joshua; Perkins, Jonathan A.; Holmes, Greg; Jabs, Ethylin W.; Cunningham, Michael L.; Dahl, John P.
Abstract : Objectives: To characterize tracheal cartilage morphology in mouse models of fibroblast growth factor receptor ( Fgfr2 )‐related craniosynostosis syndromes. To establish relationships between specific Fgfr2 mutations and tracheal cartilaginous sleeve (TCS) phenotypes in these mouse models. Methods: Postnatal day 0 knock‐in mouse lines with disease‐specific genetic variations in the Fgfr2 gene ( Fgfr2 C342Y/C342Y, Fgfr2 C342Y/+, Fgfr2 +/Y394C, Fgfr2 +/S252W, and Fgfr2 +/P253R ) as well as line‐specific controls were utilized. Tracheal cartilage morphology as measured by gross analyses, microcomputed tomography (μCT), and histopathology were compared using Chi‐squared and single‐factor analysis of variance statistical tests. Results: A greater proportion of rings per trachea were abnormal in Fgfr2 C342Y/+ tracheas (63%) than Fgfr2 +/S252W (17%), Fgfr2 +/P253R (17%), Fgfr2 +/Y394C (12%), and controls (10%) ( P < .001 for each vs. Fgfr2 C342Y/+ ). TCS segments were found only in Fgfr2 C342Y/C342Y (100%) and Fgfr2 C342Y/+ (72%) tracheas. Cricoid and first‐tracheal ring fusion was noted in all Fgfr2 C342Y/C342Y and 94% of Fgfr2 C342Y/+ samples. The Fgfr2 C342Y/C342Y and Fgfr2 C342Y/+ groups were found to have greater areas and volumes of cartilage than other lines on gross analysis and μCT. Histologic analyses confirmed TCS among the Fgfr2 C342Y/C342Y and Fgfr2 C342Y/+ groups, without appreciable differences in cartilage morphology, cell size, or density; no histologic differences were observed among other Fgfr2 lines compared to controls. Conclusion: This study found TCS phenotypes only in the Fgfr2 C342Y mouse lines. These lines also had increased tracheal cartilage compared to other mutant lines and controls. These data support further study of the Fgfr2 mouse lines and the investigation of other Fgfr2 variants to better understand their role in tracheal development and TCS formation. Level of Evidence: NA Laryngoscope, 131:E1349–E1356, 2021